Analysis of the level of community resilience to tidal flood disaster in Karangagung Village, Palang District, Tuban Regency, East Java - Nikmah, Lailatul (UIN Sunan Ampel Surabaya, 2023)
Tidal floods are inundations of water on the coastal plain due to high tide. Tidal floods are caused by tidal phenomena and excessive sea water intrusion due to rain. The level of resilience of coastal communities needs to be studied in order to minimize the impact and obtain recommendations for increasing the resilience of coastal communities to the threat of disasters. The aim of this research is to determine the level of community resilience to tidal floods in Karangagung Village, Palang District, Tuban Regency, East Java. The level of community resilience to tidal floods was analyzed using the Coastal Community Resilience (CCR) method. The results of the level of community resilience in facing tidal floods in Karangagung Village, Palang District, Tuban Regency have a value of 3.96 in the high category.